Pelaksanaan Metode Pembelajaran Inquiri untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam Kelas XI di SMKS TIK YPKP Sentani - Karfika Karfika; Moh. Y. UN. Mayalibit; Susiani Nuzum Nikmah (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This research aims to explore the teacher’s role in implementing the inquiry-based learning method to enhance students' critical thinking skills in Islamic Religious Education for grade XI AKL students at SMKS YPKP TIK Sentani. A qualitative descriptive approach was employed in this study. Data were collected through observations, interviews, and documentation. The findings reveal that teachers are crucial as planners, facilitators, and motivators in the implementation of inquiry-based learning. Key supporting factors include adequate facilities, infrastructure, and a relevant curriculum. The application of the inquiry learning method effectively improves students’ critical thinking skills by fostering activeness and learning independence. This method encourages students to explore, question, and engage with the material, leading to better understanding and application of the content. The study's implications highlight the importance of innovative teaching methods in Islamic Education and provide valuable insights for teachers seeking to improve the quality of learning and student engagement. This research is expected to serve as a reference for Islamic Education teachers in applying effective teaching strategies.